Quantification of the HIV‐1 virus‐like particle production process by super‐resolution imaging: From VLP budding to nanoparticle analysis - González‐Domínguez, Irene; Puente‐Massaguer, Eduard; Cervera, Laura; Gòdia, Francesc (Biotechnology and bioengineering, 2020)
Virus‐like particles (VLPs) offer great promise in the field of nanomedicine. Enveloped VLPs are a class of these nanoparticles and their production process occurs by a budding process, which is known to be the most critical step at intracellular level. In this study, we developed a novel imaging method based on super‐resolution fluorescence microscopy (SRFM) to assess the generation of VLPs in living cells. This methodology was applied to study the production of Gag VLPs in three animal cell platforms of reference: HEK 293‐transient gene expression (TGE), High Five‐baculovirus expression vector system (BEVS) and Sf9‐BEVS. Quantification of the number of VLP assembly sites per cell ranged from 500 to 3,000 in the different systems evaluated. Although the BEVS was superior in terms of Gag polyprotein expression, the HEK 293‐TGE platform was more efficient regarding the assembly of Gag as VLPs. This was translated into higher levels of non‐assembled Gag monomer in BEVS harvested supernatants. Furthermore, the presence of contaminating nanoparticles was evidenced in all three systems, specifically in High Five cells. The SRFM‐based method here developed was also successfully applied to measure the concentration of VLPs in crude supernatants. The lipid membrane of VLPs and the presence of nucleic acids alongside these nanoparticles could also be detected using common staining procedures. Overall, a complete picture of the VLP production process was achieved in these three production platforms. The robustness and sensitivity of this new approach broaden the applicability of SRFM toward the development of new detection, diagnosis and quantification methods based on confocal microscopy in living systems. Super‐resolution confocal microscopy is applied to three different cell production platforms to assess the Gag‐eGFP virus‐like particle (VLP) production process. The VLP assembly phenomena at intracellular level and the quality and quantity of the final VLP preparations are studied in mammalian and insect cells.